2015
DOI: 10.1016/j.atmosenv.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of atmospheric deposition of nitrogen and sulfur using ion-exchange resin collectors in Rocky Mountain National Park, USA

Abstract: h i g h l i g h t sDeposition of NO 3 À and DIN were positively related to elevation.Summer DIN deposition was 25e50% greater on the east side of the park than on the west. A high-resolution geospatial model of summer DIN deposition was created for the park. Emissions sources and climate patterns affect spatial patterns in N and S deposition. Seasonal patterns in NO 3 À isotopes may reflect variations in emissions sources. a b s t r a c tLakes and streams in Class 1 wilderness areas in the western United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…When excluding the most influencing NH 4 -N values on Pearson's r, this metric became lower ( 0.70), while better results were found for RMSE (0.29), and MFB showed and overall overestimation of NH 4 -N bulk deposition (27%). Other authors have reported similar overestimations of bulk deposition of NH 4 -N when using IECs compared to CBCs (Clow et al, 2015;Fenn and Poth, 2004;Hansen, 2012;Langlois et al, 2003). There are three main processes that could account for the discrepancy between methods: release of NH 4 þ from the amine groups of the IER, and nitrification or volatilization losses of NH 3 in the liquid samples of the CBCs (Fenn and Poth, 2004).…”
Section: Comparison Metrics and Plotsmentioning
confidence: 69%
See 1 more Smart Citation
“…When excluding the most influencing NH 4 -N values on Pearson's r, this metric became lower ( 0.70), while better results were found for RMSE (0.29), and MFB showed and overall overestimation of NH 4 -N bulk deposition (27%). Other authors have reported similar overestimations of bulk deposition of NH 4 -N when using IECs compared to CBCs (Clow et al, 2015;Fenn and Poth, 2004;Hansen, 2012;Langlois et al, 2003). There are three main processes that could account for the discrepancy between methods: release of NH 4 þ from the amine groups of the IER, and nitrification or volatilization losses of NH 3 in the liquid samples of the CBCs (Fenn and Poth, 2004).…”
Section: Comparison Metrics and Plotsmentioning
confidence: 69%
“…But the need to expand monitoring networks has impelled the use of less expensive methods, easy to operate, and without requiring frequent visits to the field (Clow et al, 2015;Erisman et al, 2005). The common alternative is using open samplers (bulk deposition collectors), which have no provision to exclude dry deposition during rainless periods.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of each sample was determined using plastic cylinders in the field, and portions of each sample were brought to the 10 laboratory for further analysis. Please note that the dry deposition flux, especially for gaseous HNO 3 , is underestimated in the NO 3 − atm deposition flux determined through this method (Aikawa et al, 2003), while the deposition flux of NO 3 − atm could be overestimated due to the progress of nitrification in sample bottles during storage in the field until recovery (Clow et al, 2015).…”
Section: Atmospheric Nitrate Deposition Ratesmentioning
confidence: 99%
“…The areal bulk deposition flux of NO 3 As presented in section 2.4, the deposition flux could be either underestimated, due to insufficient inclusion of the dry deposition flux (Aikawa et al, 2003) or overestimated, due to the progress of nitrification in sample bottles during storage in the field until recovery (Clow et al, 2015). As a 15 result, we use the bulk deposition flux determined in this study (45.6 mmol m -2 yr -1 ) as the areal total (wet + dry) deposition flux of NO 3 − atm (D atm ) at the KJ site by allowing error range of 20% in the discussions in this study.…”
Section: Atm = (F Atm T ×δT)mentioning
confidence: 99%
“…Measurements of bulk deposition of N using the IEC method showed a good agreement CBCs (Clow, et al, 2015;Fenn and Poth, 2004;Hansen, 2012;Langlois et. al., 2003).…”
Section: Comparison Metrics and Plotsmentioning
confidence: 99%